Fundamental statistics for the behavioral sciences - Howell, David C. (Belmont, California Wadsworth, Cengage Learning, 2014)
Designed as an introductory statistics course in psychology, education, and other behavioral sciences, emphasizing the logic of statistical procedures and interpretation of data rather than computational derivations.
Basic concepts -- Displaying data -- Measures of central tendency -- Measures of variability -- The normal distribution -- Basic concepts of probability -- Sampling distributions and hypothesis testing -- Correlation -- Regression -- Multiple regression -- Hypothesis testing applied to means : one sample -- Hypothesis tests applied to means : two related samples -- Hypothesis tests applied to means : two independent samples -- Power -- One-way analysis of variance -- Factorial analysis of variance factorial designs -- Repeated-measures analysis of variance -- Chi-square -- Nonparametric and distribution-free statistical tests -- Meta-analysis -- Appendix A : Arithmetic review -- Appendix B : Basic statistical formulae -- Appendix D : Data set -- Appendix E : Statistical tables.
Includes bibliographical references (pages 608-614) and index.
Keywords: Social sciences -- Statistical methods; Psychometrics